Virtuous thoughts: the philosophy of ernest sosa - Turri, John (Philosophical Studies Series, 2013)
This collection is a major contribution to the understanding and evaluation of Ernest Sosa's profound and wide-ranging philosophy, in epistemology and beyond. A balanced, fair and critical volume, it offers a sensitive appreciation of his wide philosophical purview, a nuanced assessment of the detail of his thought, and a spur to exploring the linkages between the varied topics explored by the subtle mind of this great American scholar. The papers explore a wealth of Sosa's academic interests, including his work on philosophical method, the philosophy of mind and language, metaphysics, and value theory, in addition to his output on epistemology itself. It offers, for example, a rebuttal of the counterarguments to Sosa's reliabilist theory of introspective justification, which itself concludes with some objections to Sosa's stated views on the 'speckled hen' problem. Other authors track the connections of his virtue theory to his advocacy of bi-level epistemology, provide reflections on Sosa's views on the epistemological tradition, and examine the nexus of his beliefs on intuition and philosophical methodology. This volume is an insightful reckoning of Sosa's academic account.